A new species of Trigonocorypha (Orthoptera: Tettigoniidae: Phaneropterinae) from Tamilnadu, India - Senthilkumar, Natchiappan; Divya, Govindaraj (Zootaxa, 2020)
The present study deals with description of a new species (♀) Trigonocorypha thenensis sp. nov. in the genus Trigonocorypha from Tamilnadu, India.